Autophagy Modulators and Neuroinflammation - Cho, Kyoung S.; Lee, Jang Ho; Cho, Jeiwon; Cha, Guang-Ho; Song, Gyun Jee (Current Medicinal Chemistry, 2020)
Background: Neuroinflammation plays a critical role in the development and progression of various neurological disorders. Therefore, various studies have focused on the development of neuroinflammation inhibitors as potential therapeutic tools. Recently, the involvement of autophagy in the regulation of neuroinflammation has drawn substantial scientific interest, and a growing number of studies support the role of impaired autophagy in the pathogenesis of common neurodegenerative disorders. Objective: The purpose of this article is to review recent research on the role of autophagy in controlling neuroinflammation. We focus on studies employing both mammalian cells and animal models to evaluate the ability of different autophagic modulators to regulate neuroinflammation. Methods: We have mostly reviewed recent studies reporting anti-neuroinflammatory properties of autophagy. We also briefly discussed a few studies showing that autophagy modulators activate neuroinflammation in certain conditions. Results: Recent studies report neuroprotective as well as anti-neuroinflammatory effects of autophagic modulators. We discuss the possible underlying mechanisms of action of these drugs and their potential limitations as therapeutic agents against neurological disorders. Conclusion: Autophagy activators are promising compounds for the treatment of neurological disorders involving neuroinflammation.
Keywords: autophagy modulators